An Analysis Child-Parent Relationship with Problematic Media Use - Annisa Alda Arrumdias; Sukaesi Marianti; Dita Rachmayani (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2020)
This study aims to determine the relationship between child-parent relationships with problematic media use. The method used in this study is quantitative with a correlational approach. The participants of this study were 131 parents in Malang who had children aged 6-11 years who used electronic media. The collected participants were obtained through accidental sampling technique. The research instrument used in this study is an adaptation of Child-Parent Relationship Scale and an adaptation of Problematic Media Checklist. Hypothesis analysis using Pearson Product Moment from SPSS version 24.0. Based on the hypothesis test it is known that there is a relationship between child-parent relationship and problematic media use with a significance value of 0.000 (p <0.05) and a correlation coefficient of -0.388, and there is a relationship between closeness and problematic media use subdimension with a significance value of 0.032 (p <0.05) and the correlation coefficient is -0.188, while between subdimension conflict and problematic media use there is also have a relation with a significance value of 0.000 (p <0.05) and the correlation coefficient is 0.369. The results of this study prove that there is a relationship between problematic media use and child-parent relationships, where the higher the conflict, the higher the problematic media use whereas if closeness is high then the problematic media use is low.